Microglia activation due to obesity programs metabolic failure leading to type two diabetes - Maldonado Ruiz, Roger Alexis; Montalvo Martínez, Larisa Jajaira; Fuentes Mera, Lizeth; Camacho Morales, Alberto (2017)
Obesity is an energy metabolism disorder that increases susceptibility to the development of metabolic diseases. Recently, it has been described that obese subjects have a phenotype of chronic inﬂammation in organs that are metabolically relevant for glucose homeostasis and energy. Altered expression of immune system molecules such as interleukins IL-1, IL-6, IL-18, tumor necrosis factor alpha (TNF-α), serum amyloid A (SAA), and plasminogen activator inhibitor-1 (PAI-1), among others, has been associated with the development of chronic inﬂammation in obesity. Chronic inﬂammation modulates the development of metabolic-related comorbidities like metabolic syndrome (insulin resistance, glucose tolerance, hypertension and hyperlipidemia). Recent evidence suggests that microglia activation in the central nervous system (CNS) is a priority in the deregulation of energy homeostasis and promotes increased glucose levels. This review will cover the most signiﬁcant advances that explore the molecular signals during microglia activation and inﬂammatory stage in the brain in the context of obesity, and its inﬂuence on the development of metabolic syndrome and type two diabetes.